2001
DOI: 10.1161/01.str.32.4.1000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antioxidant Therapies in Transient Focal Ischemia in Mice

Abstract: Background and Purpose-Ginkgo biloba extract (EGb) and ␣-lipoic acid (LA) are commercially available "antioxidant supplements" with a variety of actions that may be beneficial during acute stroke. These actions include inhibiting platelet and leukocyte activation and adhesion, reducing free radical generation, and increasing cerebral blood flow. Both EGb and LA have been shown to be neuroprotective in cell culture and global central nervous system ischemia models. In this study we investigated the neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
67
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 31 publications
6
67
1
Order By: Relevance
“…Therefore, as a preventive agent, LA is beneficial to cerebral I/R-induced injury. This finding is consistent with previous studies on the beneficial effects of LA against cerebral ischemia (21,22). The results demonstrated that the optimal dose of LA was 100 mg/kg.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, as a preventive agent, LA is beneficial to cerebral I/R-induced injury. This finding is consistent with previous studies on the beneficial effects of LA against cerebral ischemia (21,22). The results demonstrated that the optimal dose of LA was 100 mg/kg.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, hypoxia is likely to play an important role in neuronal death, especially at the periphery of the infarct. The in vivo neuroprotective efficacy of PAN-811 is now clearly established, and its ability to be used subsequent to arterial occlusion distinguishes it from many other neuroprotectants such as antioxidants, ginkgo biloba extract, and ␣-lipoic acid (26). It is also superior to the manganese superoxide dismutase mimetic M40401, which is reported to reduce MCAoinduced infarct volume by 73% when animals are pretreated but fails to reduce lesion volume significantly when administered subsequent to MCAo (27).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological studies performed with a cerebral ischemia model have determined pronounced contraction in neurons, irregularities in cell and nuclear margins, and perineural and pericapillary edema. Some of these studies reported a decrease in cerebral cortex and hippocampus neuron numbers and infarct in the area of ischemia (27,28). A very few studies have shown that GB has a protective effect against ischemia-associated damage in neurons.…”
Section: Discussionmentioning
confidence: 99%